BAKTI SOSIAL KHITANAN MASSAL PADA MASYARAKAT DESA TAMALATEA KECAMATAN MANUJU KABUPATEN GOWA - Kusnadi Umar; Marwah Dwi Cahyani; Dwi Wulandari Rahman; Rismawati; Andi Munifah; Muh. Amirul Haq; Ario Prasetyo Rusman; Yasrif Wildan; Muh Yusril Ihza (PPM LP2M UIN Alauddin Makassar, 2023)
Starting from the intention of fellow students to share with others, the social service activity